Low-temperature-resistant polycarbonate abrasive material and preparation method thereof

By adding silicone-polycarbonate copolymer, toughener and modified wear-resistant glass fiber to the polycarbonate abrasive, and granulation using a twin screw extruder, the polycarbonate abrasive is solved by the durability of the polycarbonate abrasive at low temperatures. The problem of poor performance achieves abrasives with good wear resistance at low temperatures.

CN119463448APending Publication Date: 2025-02-18XIAMEN YUANMI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411831320.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing polycarbonate abrasives have poor durability at low temperatures and are difficult to effectively deal with parts with high hardness and steel properties.

Method used

75-85 parts of polycarbonate, 15-20 parts of silicone-polycarbonate copolymer, 3-6 parts of toughener, 12-15 parts of modified wear-resistant glass fiber, 1-1.5 parts of coupling agent, and anti- The ratio of 0.3-0.5 parts of oxygen agent and 0.3-0.5 parts of compatible agent is melted and granulated at an extrusion temperature of 270-275℃ in the twin-screw extruder to prepare a low-temperature resistant polycarbonate abrasive.

Benefits of technology

The prepared low-temperature resistant polycarbonate abrasives exhibit excellent mechanical properties, low-temperature toughness and wear resistance at low temperatures, and can effectively treat the edges and have small wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185621420000081
    Figure BDA0005185621420000081
Patent Text Reader

Abstract

The invention relates to the field of composite materials, in particular to a low-temperature-resistant polycarbonate abrasive material and a preparation method thereof. The low-temperature-resistant polycarbonate abrasive material is prepared from the following raw materials in parts by weight: 75 to 85 parts of polycarbonate, 15 to 20 parts of organic silicon-polycarbonate copolymer, 3 to 6 parts of flexibilizer, 12 to 15 parts of modified wear-resistant glass fiber, 1 to 1.5 parts of coupling agent, 0.3 to 0.5 part of antioxidant and 0.3 to 0.5 part of compatilizer. By optimizing a formula and a process, the low-temperature-resistant polycarbonate abrasive material with excellent mechanical properties, low-temperature-resistant toughness, wear resistance and environmental protection performance is prepared, and the low-temperature-resistant polycarbonate abrasive material has a wide application prospect and an important technical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of composite materials, and in particular to a low-temperature resistant polycarbonate abrasive and a preparation method thereof. Background Art

[0002] During the injection molding process, many parts will have some flashes at their edges and corners. Manual treatment of these flashes alone is not only time-consuming, but also the appearance of the treated parts cannot be guaranteed, which may affect the appearance of the parts. Although the use of conventional abrasives to treat these flashes can meet the general flash requirements, the treatment effect is relatively poor for some more precise and demanding parts or for some parts with greater hardness and rigidity.

[0003] Polycarbonate (PC) has the characteristics of good impact resistance and high hardness, so it is widely used as an abrasive to treat flash. However, the existing polycarbonate abrasive has poor low-temperature toughness and is very easy to break at low temperatures. Treating the flash of the workpiece at low temperatures (such as -80 to -120°C) can not only easily remove the flash with high efficiency, but also effectively avoid discoloration of the workpiece due to excessive heat generation. Therefore, it is urgent to develop an abrasive with good low-temperature toughness. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present application provides a low-temperature resistant polycarbonate abrasive and a preparation method thereof. The low-temperature resistant polycarbonate abrasive prepared by the present application has excellent mechanical properties, low-temperature toughness and wear resistance, and has good comprehensive performance. In addition, the low-temperature resistant polycarbonate abrasive prepared by the present application has a good flashing effect at low temperatures and a small amount of wear.

[0005] In the first aspect, the present application provides a low-temperature resistant polycarbonate abrasive, which adopts the following technical solution: A low-temperature resistant polycarbonate abrasive comprises the following raw materials, measured by weight: 75-85 parts of polycarbonate, 15-20 parts of organosilicon-polycarbonate copolymer, 3-6 parts of toughening agent, 12-15 parts of modified wear-resistant glass fiber, 1-1.5 parts of coupling agent, 0.3-0.5 parts of antioxidant and 0.3-0.5 parts of compatibilizer.

[0006] By adopting the above technical scheme, polycarbonate: as the main component, it provides basic mechanical properties and wear resistance. Polycarbonate has good mechanical strength and wear resistance, but its low temperature performance is poor. Organosilicon-polycarbonate copolymer: the organosilicon structural unit in this copolymer has a soft Si-O-Si main chain, which provides good low temperature performance and weather resistance. At the same time, its high impact strength and good compatibility with polycarbonate help to improve the low temperature impact performance of polycarbonate. Toughening agent: the toughening agent is a core-shell structure polymer, and the polysiloxane in its core part has low temperature compliance and low surface energy, which helps to absorb and disperse impact force, thereby improving the toughness of the material. Modified wear-resistant glass fiber: through a series of treatments and modifications, the modified wear-resistant glass fiber improves dispersibility and compatibility, while maintaining its excellent mechanical properties and wear resistance. The compound use of glass fiber and nano-silica further improves the mechanical properties and wear resistance of the material. Coupling agent: the coupling agent is used to improve the compatibility between the raw materials and improve the overall performance of the composite material. Antioxidant: Antioxidant is used to protect materials from oxidation or thermal degradation and extend the service life of materials. Compatibilizer: Compatibilizer is used to improve the compatibility between different raw materials and ensure the uniformity and stability of materials. Through the synergistic effect of these raw materials, the prepared low-temperature resistant polycarbonate abrasive has excellent mechanical properties, low-temperature toughness and wear resistance, and has good comprehensive performance. At the same time, it has good flash treatment effect at low temperature and small wear, showing good application prospects.

[0007] Preferably, the method for preparing the modified wear-resistant glass fiber comprises the following steps: S21. According to the mass fraction, 100 parts of chopped glass fibers with a length of 4-6 mm and a diameter of 10-15 μm are placed in 300 parts of a 25% mass concentration hydrogen peroxide solution, and then heated at 105-110° C. for reaction for 3-4 hours; after the reaction is completed, the pre-modified glass fibers are obtained by filtering and drying; S22, according to the mass fraction, put 100 parts of the pre-modified glass fiber into 2000 parts of a polydimethyldiallylammonium chloride aqueous solution with a mass concentration of 1.7-2.0%, stir for 1-2 hours, filter, wash and dry to obtain the pre-modified glass fiber; S23. Disperse 200-250 parts of silica with an average particle size of 20-30 nanometers and 100 parts of pre-modified glass fiber in a solution consisting of 200 parts of ethanol and 500 parts of water, and stir for 2-3 hours. Then add 3.5 parts of vinyltriethoxysilane, adjust the pH of the solution to 5-6, stir for 4-5 hours, and obtain modified wear-resistant glass fiber after centrifugation, washing and drying.

[0008] By adopting the above technical scheme, glass fiber is often used to improve the mechanical strength, modulus and other properties of polycarbonate materials, but glass fiber is difficult to disperse and the use of glass fiber will increase the friction of polycarbonate composite materials and reduce the friction resistance of the material. Therefore, the glass fiber is specially modified in the present invention, specifically: the glass fiber is first treated with hydrogen peroxide, then compounded with polydimethyldiallylammonium chloride, then compounded with nano-silica, and finally modified with vinyltriethoxysilane; hydrogen peroxide treatment of glass fiber can cause oxidation on its surface, increase Strengthening its surface activity is conducive to the subsequent compounding of polydimethyldiallyl ammonium chloride. The positive charge characteristics of polydimethyldiallyl ammonium chloride and the negatively charged nano-silica on the surface can be effectively compounded and combined; and the hydroxyl groups on the surface of the glass fiber treated with nano-silica and hydrogen peroxide can produce hydrogen bonds with polydimethyldiallyl ammonium chloride, which strengthens the stability of the compounding system. Finally, after modification with vinyl triethoxysilane, the dispersibility and compatibility of the modified wear-resistant glass fiber can be significantly improved, thereby significantly improving the mechanical properties and low-temperature wear resistance of polycarbonate abrasives. In addition, the compounding of glass fiber and nano-silica, on the one hand, improves the dispersibility of glass fiber and other problems, and ensures the effect of glass fiber on improving the mechanical properties of polycarbonate composite materials; on the other hand, as an excellent filler particle, nano-silica can reduce its tendency to agglomerate when compounded with glass fiber, ensuring that it plays a dual role in improving the mechanical properties and wear resistance of polycarbonate.

[0009] Preferably, the method for preparing the toughening agent comprises the following steps: S31, dissolving 5-8 parts of behenyltrimethylammonium chloride and 1.5-2 parts of fatty alcohol polyoxyethylene ether AEO-3 in 500 parts of deionized water according to their mass proportions, heating to 45-50° C., then adding 25-30 parts of 1,4-butanediol and 25-30 parts of terephthalic acid, stirring at a speed of 500-600 rpm for 30-40 min to obtain a mixed solution A; S32, according to the mass fraction, adjusting the speed to 200-250rpm, raising the temperature to 70-80°C, adding a 0.2% azobisisobutyronitrile aqueous solution dropwise to the mixed solution A, cooling to 60-70°C, adding a 1 mol / L sodium hydroxide aqueous solution, adjusting the pH to 9-12, and obtaining a polybutylene terephthalate emulsion; S33, dissolving fatty alcohol polyoxyethylene ether AEO-3 in deionized water according to the mass fraction, adding octamethylcyclotetrasiloxane and silane coupling agent, stirring at a speed of 500-600 rpm for 30-40 min, to obtain a mixed solution B; S34. Add 80 parts of mixed solution B dropwise into 100 parts of polybutylene terephthalate emulsion according to the mass fractions, react at 60-70° C. for 1-2 hours, raise the temperature to 75-80° C. for 1-2 hours, and obtain a toughening agent.

[0010] By adopting the above technical scheme, the prepared toughening agent is a core-shell structure polymer with polysiloxane as the core and polybutylene terephthalate as the shell, wherein the polysiloxane as the core has low-temperature compliance and low surface energy, and can act as a stress concentration point when the polycarbonate resin matrix is ​​subjected to external impact force, thereby causing the generation of triaxial tensile stress in the surrounding polycarbonate resin matrix, causing the interface between the polysiloxane and the polycarbonate resin matrix to debond and form holes, thereby hindering the formation and expansion of cracks inside the polycarbonate resin matrix, thereby improving the toughness of the polycarbonate composite material in a low-temperature environment.

[0011] Preferably, in step S32, the mass ratio of the mixed solution A, the aqueous solution of azobisisobutyronitrile and the aqueous solution of sodium hydroxide is 80-100:0.04-0.05:0.007-0.01.

[0012] Preferably, in step S33, the silane coupling agent is composed of γ-aminopropyltrimethoxysilane and N-aminoethyl-γ-aminopropyltriethoxysilane in a mass ratio of 3:2.

[0013] Preferably, in step S33, the mass ratio of the fatty alcohol polyoxyethylene ether AEO-3, ionized water, octamethylcyclotetrasiloxane and silane coupling agent is 18:500:150-200:30-40.

[0014] Preferably, the coupling agent is composed of γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane in a mass ratio of 1:1.

[0015] By adopting the above technical scheme, γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane as coupling agents can effectively improve the interfacial compatibility between polycarbonate and modified wear-resistant glass fiber. Through chemical bonding or physical adsorption, they can form a stable bridge between organic polymers and inorganic fillers, thereby improving the overall performance of the composite material. Due to the presence of the coupling agent, the modified wear-resistant glass fiber can be more evenly dispersed in the polycarbonate resin, avoiding the occurrence of agglomeration. This not only helps to improve the mechanical strength of the material, but also enhances its wear resistance. Under low temperature conditions, the material often becomes fragile and easy to crack. The coupling agent helps to improve the toughness of the polycarbonate composite material at low temperatures and reduce the formation and expansion of cracks by optimizing the interaction between the modified wear-resistant glass fiber and the matrix resin. The combined use of γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane may produce a synergistic effect, further enhancing the above-mentioned properties. The two different coupling agents may complement each other at the molecular level, providing a more comprehensive and balanced interface modification effect. In summary, γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane, as coupling agents, play a vital role in the preparation of low-temperature resistant polycarbonate abrasives. They not only improve the mechanical properties and wear resistance of the material, but also significantly improve its toughness in low-temperature environments.

[0016] Preferably, the compatibilizer is ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate, and the glycidyl methacrylate grafting rate of the ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate is 1.0-1.6%.

[0017] By adopting the above technical scheme, the compatibilizer is ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate having active epoxy groups, which can react with the terminal hydroxyl groups and terminal carboxyl groups of polycarbonate and silicone-polycarbonate copolymer to improve the compatibility and interfacial adhesion of the two. At the same time, the structural unit of ethylene-methyl acrylate copolymer has relatively high impact strength at room temperature and low temperature, which is beneficial to improving the low-temperature impact performance of polycarbonate abrasive.

[0018] Preferably, the antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

[0019] In a second aspect, the present application provides a method for preparing a low-temperature resistant polycarbonate abrasive, which adopts the following technical scheme: As a general technical concept, the present application also provides a method for preparing the above-mentioned low-temperature resistant polycarbonate abrasive, comprising the following steps: S101, according to the mass fractions, polycarbonate, silicone-polycarbonate copolymer, toughening agent, modified wear-resistant glass fiber, coupling agent, antioxidant and compatibilizer are stirred and mixed uniformly to obtain a premix; S102, melting the premix at an extrusion temperature of 270-275° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 400-450 rpm to obtain a low-temperature resistant polycarbonate abrasive.

[0020] In summary, the present application includes at least one of the following beneficial technical effects: 1. Excellent mechanical properties and low temperature toughness: The mechanical properties and low temperature toughness of polycarbonate abrasives are improved by adding silicone-polycarbonate copolymers and toughening agents. The softness and high and low temperature resistance of silicone structural units, as well as the low temperature compliance and low surface energy characteristics of polysiloxane in the toughening agent, work together on polycarbonate abrasives, allowing them to maintain good toughness even in low temperature environments.

[0021] 2. Improvement of wear resistance: The use of modified wear-resistant glass fiber enhances the wear resistance of abrasives. Through hydrogen peroxide treatment and subsequent composite modification, the dispersibility and compatibility of modified wear-resistant glass fiber are significantly improved, thereby improving the wear resistance of abrasives.

[0022] 3. Low-temperature treatment flashing effect and wear control: The low-temperature resistant polycarbonate abrasive prepared in the present application has a good flashing effect and small wear at low temperatures, which shows that it has high practical value and good economic benefits in practical applications.

[0023] 4. Improvement of compatibility and interfacial adhesion: The use of compatibilizer improves the compatibility and interfacial adhesion between polycarbonate and silicone-polycarbonate copolymer, which is of great significance for improving the overall performance and stability of the material. DETAILED DESCRIPTION

[0024] The implementation scheme of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. The silicone-polycarbonate copolymer was purchased from Saudi Basic Industries Corporation; the ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate had a glycidyl methacrylate grafting rate of 1.2%, which was purchased from Arkema, France.

[0025] In the following examples and preparation examples, 1 part means 100 g.

[0026] Preparation Example 1 Preparation of modified wear-resistant glass fiber The preparation method of modified wear-resistant glass fiber comprises the following steps: S21. According to the mass fraction, 100 parts of chopped glass fibers with a length of 4-6 mm and a diameter of 10-15 μm are placed in 300 parts of a 25% hydrogen peroxide solution, and then heated at 108° C. for 3.4 hours. After the reaction is completed, the pre-modified glass fibers are obtained by filtering and drying. S22, according to the mass fraction, put 100 parts of the pre-modified glass fiber into 2000 parts of a 1.8% polydimethyldiallylammonium chloride aqueous solution, stir for 1.5 hours, filter, wash and dry to obtain the pre-modified glass fiber; S23. According to the mass proportions, 230 parts of silica with an average particle size of 20 nanometers and 100 parts of pre-modified glass fibers are dispersed in a solution consisting of 200 parts of ethanol and 500 parts of water, and stirred for 2.5 hours. Then, 3.5 parts of vinyltriethoxysilane are added thereto, and the pH of the solution is adjusted to 5.5. The solution is stirred for 4.5 hours. After centrifugation, washing and drying, modified wear-resistant glass fibers are obtained.

[0027] Preparation Example 2 Preparation of toughening agent The preparation method of the toughening agent comprises the following steps: S31, dissolving 7 parts of behenyltrimethylammonium chloride and 1.8 parts of fatty alcohol polyoxyethylene ether AEO-3 in 500 parts of deionized water according to their mass parts, heating to 48° C., then adding 28 parts of 1,4-butanediol and 28 parts of terephthalic acid, stirring at a speed of 550 rpm for 35 min to obtain a mixed solution A; S32, according to the mass fraction, adjusting the speed to 230 rpm, raising the temperature to 78° C., adding dropwise 0.045 parts of a 0.2% aqueous solution of azobisisobutyronitrile to 90 parts of mixed solution A, and when the temperature is lowered to 65° C., adding 0.009 parts of a 1 mol / L aqueous solution of sodium hydroxide, adjusting the pH to 10, and obtaining a polybutylene terephthalate emulsion; S33, dissolving 18 parts of fatty alcohol polyoxyethylene ether AEO-3 in 500 parts of deionized water, adding 180 parts of octamethylcyclotetrasiloxane and 35 parts of silane coupling agent, stirring at a speed of 550 rpm for 35 min to obtain a mixed solution B; the silane coupling agent is composed of γ-aminopropyltrimethoxysilane and N-aminoethyl-γ-aminopropyltriethoxysilane in a mass ratio of 3:2; S34. Add 80 parts of mixed solution B dropwise into 100 parts of polybutylene terephthalate emulsion according to the mass fractions, react at 65° C. for 1.2 h, heat to 78° C. for 1.5 h, and obtain a toughening agent.

[0028] Example 1 A low-temperature resistant polycarbonate abrasive, comprising the following raw materials by weight: 75 parts of polycarbonate, 15 parts of organosilicon-polycarbonate copolymer, 3 parts of toughening agent, 12 parts of modified wear-resistant glass fiber, 1 part of coupling agent, 0.3 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite and 0.3 parts of ethylene-methyl acrylate copolymer grafted glycidyl methacrylate as antioxidant, wherein the coupling agent is composed of γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane in a weight ratio of 1:1; The method for preparing the low temperature resistant polycarbonate abrasive comprises the following steps: S101, according to the mass proportions, polycarbonate, organosilicon-polycarbonate copolymer, toughening agent, modified wear-resistant glass fiber, coupling agent, antioxidant bis(2,4-dicumylphenyl)pentaerythritol diphosphite and ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate are stirred and mixed uniformly to obtain a premix; S102, melting the premix at an extrusion temperature of 270° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 400 rpm to obtain a low-temperature resistant polycarbonate abrasive.

[0029] Example 2 A low-temperature resistant polycarbonate abrasive, comprising the following raw materials by weight: 85 parts of polycarbonate, 20 parts of organosilicon-polycarbonate copolymer, 6 parts of toughening agent, 15 parts of modified wear-resistant glass fiber, 1.5 parts of coupling agent, 0.5 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite and 0.5 parts of ethylene-methyl acrylate copolymer grafted glycidyl methacrylate as antioxidant, wherein the coupling agent is composed of γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane in a weight ratio of 1:1; The method for preparing the low temperature resistant polycarbonate abrasive comprises the following steps: S101, according to the mass proportions, polycarbonate, organosilicon-polycarbonate copolymer, toughening agent, modified wear-resistant glass fiber, coupling agent, antioxidant bis(2,4-dicumylphenyl)pentaerythritol diphosphite and ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate are stirred and mixed uniformly to obtain a premix; S102, melting the premix at an extrusion temperature of 275° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 450 rpm to obtain a low-temperature resistant polycarbonate abrasive.

[0030] Example 3 A low-temperature resistant polycarbonate abrasive, comprising the following raw materials by weight: 80 parts of polycarbonate, 18 parts of organosilicon-polycarbonate copolymer, 4 parts of toughening agent, 14 parts of modified wear-resistant glass fiber, 1.3 parts of coupling agent, 0.4 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite and 0.4 parts of ethylene-methyl acrylate copolymer grafted glycidyl methacrylate as antioxidant, wherein the coupling agent is composed of γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane in a weight ratio of 1:1; The method for preparing the low temperature resistant polycarbonate abrasive comprises the following steps: S101, according to the mass proportions, polycarbonate, organosilicon-polycarbonate copolymer, toughening agent, modified wear-resistant glass fiber, coupling agent, antioxidant bis(2,4-dicumylphenyl)pentaerythritol diphosphite and ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate are stirred and mixed uniformly to obtain a premix; S102, melting the premix at an extrusion temperature of 273° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 430 rpm to obtain a low-temperature resistant polycarbonate abrasive.

[0031] Comparative Example 1 The same as Example 3, except that: 98 parts of polycarbonate and 0 parts of organosilicon-polycarbonate copolymer.

[0032] Comparative Example 2 The same as Example 3, except that an equal amount of a mixture (made by mixing short glass fibers having a length of 4-6 mm and a diameter of 10-15 μm and silicon dioxide having an average particle size of 20 nm in a mass ratio of 100:13) is used instead of the modified wear-resistant glass fibers.

[0033] Comparative Example 3 The same as Example 3, except that: the coupling agent is γ-aminopropyltrimethoxysilane.

[0034] Comparative Example 4 The same as Example 3, except that: the coupling agent is anilinemethyltriethoxysilane.

[0035] Comparative Example 5 The same as Example 3, except that the toughening agent is replaced by polysiloxane of the same molecular weight.

[0036] Comparative Example 6 The same as Example 3, except that the toughening agent is replaced by polybutylene terephthalate of the same molecular weight.

[0037] Comparative Example 7 The same as Example 3, except that the toughening agent is replaced by a mixture of polysiloxane and polybutylene terephthalate with equal total mass and a mass ratio of 1:1.

[0038] Performance testing The low-temperature resistant polycarbonate abrasive samples prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 7 were respectively sampled and injection-molded into test bars. The following tests were performed. The results are shown in Table 1.

[0039] Tensile strength: tested according to GB / T1040-2006 standard, the tensile rate is 50mm / min; tested at room temperature at 23℃ and low temperature at 60℃; Notched impact strength: tested according to GB / T1843-2008 standard; Abrasion resistance: Tested in accordance with GB / T 3960-2016; Treatment of flashing effect and abrasive wear: Put the workpiece to be treated and the polycarbonate abrasive into a stainless steel hollow basket, use liquid nitrogen as the freezing treatment medium, when the temperature reaches -100℃, turn on the power equipment of the flashing treatment to make the polycarbonate abrasive impact the flashing of the workpiece. After 4 hours, observe the flashing treatment effect and the change in the appearance of the abrasive, and have 8 professionals score them on a scale of 1-10, and take the average score. The higher the score, the better the flashing treatment effect and the higher the wear resistance.

[0040] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The low-temperature resistant polycarbonate abrasives prepared in Examples 1 to 3 have excellent mechanical properties, low-temperature toughness and wear resistance, and good comprehensive performance. In addition, the low-temperature resistant polycarbonate abrasives prepared in this application have good flashing effect at low temperatures and small wear.

[0041] 2) The performance comparison analysis of the low-temperature resistant polycarbonate abrasive prepared in Example 3 and Comparative Example 1 shows that the silicone structural unit in the added silicone-polycarbonate copolymer has a soft Si-O-Si main chain, and the characteristics of the Si-O-Si main chain are high and low temperature resistance, weather resistance, hydrophobicity and low viscosity, which is highly complementary to the polycarbonate structural unit with large steric hindrance and poor processing performance. In addition, the silicone-polycarbonate copolymer has high room temperature and low temperature impact strength, good compatibility with polycarbonate resin, and is beneficial to improving the low-temperature impact performance of polycarbonate resin.

[0042] 3) The performance comparison analysis of the low-temperature resistant polycarbonate abrasive prepared in Example 3 and Comparative Example 2 shows that the modified wear-resistant glass fiber prepared in the present application: the glass fiber is first treated with hydrogen peroxide, then compounded with polydimethyldiallyl ammonium chloride, then compounded with nano-silica, and finally modified with vinyltriethoxysilane; hydrogen peroxide treatment of the glass fiber can oxidize its surface and enhance its surface activity, which is beneficial to the subsequent compounding of polydimethyldiallyl ammonium chloride, and the positive charge characteristics of polydimethyldiallyl ammonium chloride and the nano-silica with negative surface charge can be effectively compounded and combined; and the hydroxyl groups on the surface of the glass fiber after nano-silica and hydrogen peroxide treatment can produce hydrogen bonds with polydimethyldiallyl ammonium chloride in pairs, thereby enhancing the stability of the compounding system, and finally modified with vinyltriethoxysilane, which can significantly improve the dispersibility and compatibility of the modified wear-resistant glass fiber, thereby significantly improving the mechanical properties and low-temperature wear resistance of the polycarbonate abrasive.

[0043] 4) The performance comparison analysis of the low-temperature resistant polycarbonate abrasive prepared by Example 3 and Comparative Examples 3-4 shows that the coupling agent is composed of γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane in a mass ratio of 1:1. The coupling agent can effectively improve the interfacial compatibility between polycarbonate and modified wear-resistant glass fiber. Through chemical bonding or physical adsorption, they can form a stable bridge between organic polymers and inorganic fillers, thereby improving the overall performance of the composite material. Due to the presence of the coupling agent, the modified wear-resistant glass fiber can be more evenly dispersed in the polycarbonate resin, avoiding the occurrence of agglomeration. This not only helps to improve the mechanical strength of the material, but also enhances its wear resistance. Under low temperature conditions, the material often becomes fragile and easy to crack. The coupling agent helps to improve the toughness of the polycarbonate composite material at low temperatures and reduce the formation and expansion of cracks by optimizing the interaction between the modified wear-resistant glass fiber and the matrix resin. By utilizing the synergistic effect between γ-aminopropyltrimethoxysilane and anilinemethyltriethoxysilane, not only the mechanical properties and wear resistance of the material are improved, but also its toughness in low temperature environments is significantly improved.

[0044] 5) The comparative analysis of the performance of the low-temperature resistant polycarbonate abrasives prepared in Example 3 and Comparative Examples 5-7 shows that the toughening agent prepared in the present application is a core-shell structure polymer, wherein the polysiloxane as the core has low-temperature compliance and low surface energy, and can act as a stress concentration point when the polycarbonate resin matrix is ​​subjected to external impact force, thereby causing the generation of triaxial tensile stress in the surrounding polycarbonate resin matrix, causing the interface between the polysiloxane and the polycarbonate resin matrix to debond and form holes, thereby hindering the formation and expansion of cracks inside the polycarbonate resin matrix, thereby improving the toughness of the polycarbonate composite material in a low-temperature environment.

[0045] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A low temperature resistant polycarbonate abrasive, characterized in that: The preparation raw materials include, by weight: 75-85 parts of polycarbonate, 15-20 parts of organosilicon-polycarbonate copolymer, 3-6 parts of toughening agent, 12-15 parts of modified wear-resistant glass fiber, 1-1.5 parts of coupling agent, 0.3-0.5 parts of antioxidant and 0.3-0.5 parts of compatibilizer.

2. The low temperature resistant polycarbonate abrasive according to claim 1, characterized in that: The method for preparing the modified wear-resistant glass fiber comprises the following steps: S21. According to the mass fraction, 100 parts of chopped glass fibers with a length of 4-6 mm and a diameter of 10-15 μm are placed in 300 parts of a 25% mass concentration hydrogen peroxide solution, and then heated at 105-110° C. for reaction for 3-4 hours; after the reaction is completed, the pre-modified glass fibers are obtained by filtering and drying; S22, according to the mass fraction, put 100 parts of the pre-modified glass fiber into 2000 parts of a polydimethyldiallylammonium chloride aqueous solution with a mass concentration of 1.7-2.0%, stir for 1-2 hours, filter, wash and dry to obtain the pre-modified glass fiber; S23. Disperse 200-250 parts of silica with an average particle size of 20-30 nanometers and 100 parts of pre-modified glass fiber in a solution consisting of 200 parts of ethanol and 500 parts of water, and stir for 2-3 hours. Then add 3.5 parts of vinyltriethoxysilane, adjust the pH of the solution to 5-6, stir for 4-5 hours, and obtain modified wear-resistant glass fiber after centrifugation, washing and drying.

3. The low temperature resistant polycarbonate abrasive according to claim 1, characterized in that: The preparation method of the toughening agent comprises the following steps: S31, dissolving 5-8 parts of behenyltrimethylammonium chloride and 1.5-2 parts of fatty alcohol polyoxyethylene ether AEO-3 in 500 parts of deionized water according to their mass proportions, heating to 45-50° C., then adding 25-30 parts of 1,4-butanediol and 25-30 parts of terephthalic acid, stirring at a speed of 500-600 rpm for 30-40 min to obtain a mixed solution A; S32, according to the mass fraction, adjusting the speed to 200-250rpm, raising the temperature to 70-80°C, adding a 0.2% azobisisobutyronitrile aqueous solution dropwise to the mixed solution A, cooling to 60-70°C, adding a 1 mol / L sodium hydroxide aqueous solution, adjusting the pH to 9-12, and obtaining a polybutylene terephthalate emulsion; S33, dissolving fatty alcohol polyoxyethylene ether AEO-3 in deionized water according to the mass fraction, adding octamethylcyclotetrasiloxane and silane coupling agent, stirring at a speed of 500-600 rpm for 30-40 min, to obtain a mixed solution B; S34. Add 80 parts of mixed solution B dropwise into 100 parts of polybutylene terephthalate emulsion according to the mass fractions, react at 60-70° C. for 1-2 hours, raise the temperature to 75-80° C. for 1-2 hours, and obtain a toughening agent.

4. The low temperature resistant polycarbonate abrasive according to claim 3, characterized in that: In step S32, the mass ratio of the mixed solution A, the aqueous solution of azobisisobutyronitrile and the aqueous solution of sodium hydroxide is 80-100:0.04-0.05:0.007-0.

01.

5. The low temperature resistant polycarbonate abrasive according to claim 3, characterized in that: In step S33, the silane coupling agent is composed of γ-aminopropyltrimethoxysilane and N-aminoethyl-γ-aminopropyltriethoxysilane in a mass ratio of 3:

2.

6. The low temperature resistant polycarbonate abrasive according to claim 3, characterized in that: In step S33, the mass ratio of the fatty alcohol polyoxyethylene ether AEO-3, ionized water, octamethylcyclotetrasiloxane and silane coupling agent is 18:500:150-200:30-40.

7. The low temperature resistant polycarbonate abrasive according to claim 1, characterized in that: The coupling agent is composed of gamma-aminopropyltrimethoxysilane and anilinomethyltriethoxysilane in a mass ratio of 1:

1.

8. The low temperature resistant polycarbonate abrasive according to claim 1, characterized in that: The compatibilizer is ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate, and the glycidyl methacrylate grafting rate of the ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate is 1.0-1.6%.

9. The low temperature resistant polycarbonate abrasive according to claim 1, characterized in that: The antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

10. A method for preparing a low-temperature resistant polycarbonate abrasive according to any one of claims 1 to 9, characterized in that: The following steps are involved: S101, mixing polycarbonate, organosilicon-polycarbonate copolymer, toughening agent, modified wear-resistant glass fiber, coupling agent, antioxidant and compatibilizer uniformly according to weight proportions to obtain a premix; S102, melting the premix at an extrusion temperature of 270-275° C. in a twin-screw extruder, extruding and granulating the premix at a rotation speed of 400-450 rpm to obtain a low-temperature resistant polycarbonate abrasive.

Citation Information

Cited By

  • Acrylic plate with fluorescent function and preparation method thereof

    CN119775465A

  • Composite material as well as preparation method and application thereof

    CN120648251A

  • Composite material, method for producing same, and use thereof

    CN120648251B